Pandemic Populism? How Covid-19 Triggered Populist Facebook User Comments in Germany and Austria - Thiele, Daniel (2022)
Covid-19 and the government measures taken to combat the pandemic have fueled populist protests in Germany and Austria. Social media played a key role in the emergence of these protests. This study argues that the topic of Covid-19 has triggered populist user comments on Facebook pages of German and Austrian mass media. Drawing on media psychology, this article theorizes populist comments as an expression of “reactance,” sparked by repeated “fear appeals” in posts about Covid-19. Several hypotheses are derived from this claim and tested on a dataset of N = 25,121 Facebook posts, posted between January 2020 and May 2021 on nine pages of German and Austrian mass media, and 1.4 million corresponding user comments. To measure content-based variables automatically, this study develops, validates, and applies dictionaries. The study finds that the topic of Covid-19 did trigger populist user comments and that this effect grew over time. Surprisingly, neither the stringency of government measures nor mentions of elitist actors were found to have the expected amplifying effect. The study discusses the findings against the background of governing the ongoing crisis and worrisome developments in the online public sphere.